Meningkatkan Hasil Belajar Siswa Dan Keaktifan Siswa Menggunakan Model Problem Based Learning (PBL) - Haslinda Haslinda; Muhammad Dahlan; Hanana Muliana (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
The research approach used is Classroom Action Research which is carried out in 2 cycles where each cycle is as many as 4 meetings, as for the learning steps given in the classroom action research approach, namely paying attention to teacher explanations, asking questions during discussions, collaborating with groups, presenting results and concluding material.The results showed that there was an increase in student learning outcomes seen from the test results obtained by students each cycle increased, besides that student activity in the classroom also increased. This can be seen from the number of percentages in the first cycle of the first meeting only got a percentage of 57.6% and 84.61% in the second meeting in the second cycle of the previous one, this is because students do not understand the Problem Based Learning (PBL) learning model. It was concluded that by using the Problem Based Learning (PBL) model. In learning Civics class IV UPT SPF SD Inpres Bontomanai is able to improve student learning outcomes.